2018
DOI: 10.1097/scs.0000000000004681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Airway Volume in Cleft Lip and Palate Following Nasoalveolar Molding

Abstract: Patients with cleft lip and palate (CLP) have commonly reduced nasal airways and are more prone to snoring, mouth breathing and hypopnea during sleep. Therefore, the morphometric evaluation of pharyngeal airway in patients with CLP is crucial. The purpose of this study is to evaluate the pharyngeal airway volumes of patients with CLP who underwent nasoalveolar molding (NAM) and to compare them with a well-matched control group without NAM. The study consisted of 40 patients with CLP divided into 2 main groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The results of our study showed that group 1 had an increase in volume and area of upper airway compared to group 2. Our results are in concurrence with the findings of a CBCT-based clinical study, which observed a significant increase in nasopharyngeal airway dimensions (Astani et al, 2018) and higher oxygen saturation (Yilmaz et al, 2017) in patients who had undergone NAM during infancy. However, there is lack of such studies that limit us to correlate with these studies only.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of our study showed that group 1 had an increase in volume and area of upper airway compared to group 2. Our results are in concurrence with the findings of a CBCT-based clinical study, which observed a significant increase in nasopharyngeal airway dimensions (Astani et al, 2018) and higher oxygen saturation (Yilmaz et al, 2017) in patients who had undergone NAM during infancy. However, there is lack of such studies that limit us to correlate with these studies only.…”
Section: Discussionsupporting
confidence: 92%
“…Systematic reviews and meta-analysis on long-term outcome of PSIO and NAM do not show significant effects when compared to each other or to no treatment, in terms of feeding, general body growth, facial aesthetics, maxillary arch dimension, speech as well as adverse effects and problems. However, the parameters of nasolabial aesthetics and airway showed significant positive changes (Uzel et al, 2011; Papadopoulos et al, 2012; Hosseini et al, 2017; Astani et al, 2018). Group 1 of the study sample had undergone NAM procedure during their infancy, and the present study aimed at adding evidence to same with help of a nonionizing and noninvasive modality of ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional technology (CAD-CAM) is one of the developed techniques for medical imaging in which laser surface scanning is applied for obtaining three-dimensional images and providing high-accuracy measurements from the defined sites. This study was an evaluation of the pre-surgical cleft treatment using a CAM system (36). We found two prospectivecomparative studies confirming CAD systems as reliable techniques for the evaluation and quantification of the nasal and alveolar improvement following NAM therapy (17, 24).…”
Section: Three-dimensional Technologymentioning
confidence: 79%
“…Deficiency of growth and development in the midfacial complex is a major drawback of primary CLP repair in the neonatal period of growth, well documented in the literature [1][2][3]. Causes are thought to be formation of scar tissue in the growth centers of the maxilla [4], mouth breathing due to obstruction of the nasal passage [5], deficiency of the alveolar process due to missing teeth [6], and a tense upper lip [7,8]. Unrepaired bone defects on the other hand result in closer to normal maxillo-facial development [7,8].…”
Section: Introductionmentioning
confidence: 99%